Functional capability is enhanced with semitendinosus than patellar tendon ACL repair - Rudroff, T. (Medicine & Science in Sports & Exercise, 2003)
The patellar and semitendinosus tendon autograft are the two most common techniques that orthopedic surgeons use to reconstruct the anterior cruciate ligament (ACL). It has not been established, however, whether either of these techniques provides a greater functional advantage to the patient. PURPOSE: To identify patients' functional capabilities after reconstruction of the ACL with a patellar or semitendinosus tendon autograft. METHODS: Forty male soccer players volunteered for the study and were assigned to three homogeneous groups: individuals who had patellar tendon reconstruction (N = 15), individuals who had semitendinosus tendon reconstruction (N = 15), and a control group (N = 10). All patients had undergone surgery 2 yr before this study and received the same rehabilitation training. The testing procedures included measurement of thigh circumference, maximal isometric strength of quadriceps and hamstrings, two- and one-legged jump, squat and gait analysis. Kinetic, kinematic, and electromyographic data were collected. RESULTS: The patellar tendon group exhibited lower (P < 0.05) coactivation of the agonist and antagonist muscles around the knee joint during the squat movement and lower stabilization- and landing degrees during the jumps. Furthermore, the patellar tendon group had a shorter stance phase and reached the first vertical maximum later with the impaired leg while walking (720.2 +/- 15.6 ms vs 740.3 +/- 14.3 ms, and 24.3 +/- 0.64% vs 22.9 +/- 0.74% of stance phase), which was not observed in the semitendinosus tendon and control groups. CONCLUSION: Functional performance is compromised in patients who undergo a patellar tendon graft compared with a semitendinosus graft, possibly due to an altered activation of the quadriceps and hamstring muscles.